Ur in the twenty-first century CE: proceedings of the 62nd Rencontre assyriologique internationale at Philadelphia, July 11-15, 2016 - Frame, Grant; Jeffers, Joshua; Pittman, Holly (Eisenbrauns, 2021)
"Papers presented at the 62nd Rencontre Assyriologique Internationale, held in Philadelphia on July 11-15, 2016, examining archaeological, artistic, cultural, economic, historical, and textual matters related to the ancient city of Ur in southern Iraq"--